The Epidemiology of Epileptic Spasm and Affecting Factors on One-Year Prognosis: A Study in Tabriz Children’s Hospital - Sadeghvand, Shahram; Kamali, Ali; Mosavi, Mirhadi; Mahallei , Majid; shiva, Shadi; Magsudy, Amin; Ahmadi Hajkolaie, Fatemeh; Erabi , Gisou; Dadashzadeh asl, Amirhosein (Iranian Journal of Child Neurology, 2025)
Objectives: Epileptic Spasm (ES) is a special type of convulsive disorder that primarily occurs in infants, typically within the first year of life. This disorder is usually resistant to routine anticonvulsant drugs. This study aims to evaluate the epidemiology and factors affecting one-year prognosis in patients with ES in Tabriz Children’s Hospital. Materials & Methods: This descriptive-analytical cross-sectional study focused on patients diagnosed with ES who were referred to the neurology department of Tabriz Children’s Hospital between 2015 and 2019. Data was collected using a census sampling method and a checklist that included demographic information and clinical and treatment histories. The results were then reported statistically. Results: Thirty-seven patients were studied, with 15 (40.5%) exhibiting flexor seizures, eight (21.7%) extensor seizures, and 14 (37.8%) mixed seizures. The most common causes were prenatal insult (10 cases, 27.0%), cryptogenic (9 cases, 24.3%), and Central Nervous System (CNS) malformations (6 cases, 16.2%). Electroencephalography findings included modified hypsarrhythmia in 12 cases (30.8%), hypsarrhythmia in 16 (41.0%), and frequent epileptiform discharge in nine (23.1%). MRI and CT scans showed abnormalities in three cases (8.1%) and 16 cases (43.2%), respectively. Treatment involved Phenobarbital in 35 patients (94.6%), Vigabatrin in 29 (78.4%), and ACTH in 11 (29.7%). The one-year prognosis indicated 25 patients (67.6%) experienced disease recurrence, seven (18.9%) recovered with complications, and two (5.4%) died. Conclusion: The most common causes of ES are prenatal insults, cryptogenic factors, and CNS malformations. The key one-year prognoses include disease recurrence and recovery with complications.